Il contributo dell’Università per lo sviluppo sociale - Fisichella, Mons Rino (Alpha omega, 2018)
Following the indications provided by Benedict XVI in Caritas in veritate, the author analyses the characteristics of contemporary culture and the mission of the university within that culture. In a world marked by globalisation, by the development of technology and of communication, there is a greater risk of thought becoming superficial and of relativism, with the result that ethics risks collapsing into a materialistic utilitarianism, involving serious dangers for human life, for the family and for the environment. The university will have to be capable of forming people who are capable of serious thought and of deep reflection, with a passion for the truth, and yet who are capable at the same time of expounding that truth calmly and with kindness, in a world that is also marked by a digital culture. Research into the foundations of the dignity of the human person, justice and peace, will lead to a culture in which there is a place for God in the public realm and an existential openness to the encounter with the truth of Christ.